The U.S Foreign Policy in the Middle East post 9/11 Case study: Iraq war 2003 - ACHOUR, ABDEKADER; HILOUFA ,MOHAMED NADIR; NEBEG, RAOUF (Faculty of Letters and Foreign Languages Department of English, 2019)
The foreign policy of the United States is the policy by which the United States deals with foreign countries. The U.S. is still considered as the only superpower in the world. The main objective of the U.S. foreign policy is to create a secure and democratic world for all the American people and international community. This study undertakes to examine the United States foreign policy in the Middle East after the incident of September 11, 2001 and what are the main reasons that led to the invasion of Iraq in 2003. Many politicians, scholars and journalists argue that there is a clear discrepancy between claimed U.S. ideals and its actions; that human rights, justice and self-determination are victims of national interests and that restoring things to what's right is all that matters U.S. foreign policy. This research seeks to investigate whether U.S. foreign policy towards the Middle East after 9/11including the invasion of Iraq was a reaction to that incident. The thesis is based on two assumptions; the U.S. professes high standards and acts in double standards, and the U.S pretends to export its values but basically seeks to extend its rule more broadly in order to preserve the privileges gained after the collapse of the USSR. In an attempt to uncover the underlying causes of the U.S. foreign policy, we took Iraq war as case study. This work uses the present study to compare the agenda of American democracy with its real interests. In addition, this work uses a historical research approach to provide a comprehensive analysis. One of the main findings of this research is that the claims made by the Bush administration to wage wars on Afghanistan and Iraq proved to be illusory. The US military and foreign policies are causing chaos. . Eventually, the thesis looks into the severe violations on the right of Iraqis and aims at clarifying and uncover the oil cartels' greed, consequently, reaching the real ends behind the war on Iraq. The only way for America to reduce the negative image and restore the world's confidence in it and to respect its foreign policy again is to get rid of egoism and its self-serving attitude, and to stand on the same distance between all parties - Muslims and Jews - stop the use of power and believe in a world shared with others so as not to be dominated.